Design and Performance of Anticracking Asphalt-Treated Base. (22nd May 2017) - Tian, Xiaoge; Han, Haifeng; Zhang, Qisen; Li, Xinwei; Li, Ye
Abstract : To enhance the crack resistance of asphalt-treated base (ATB), a type of gapped and semiopened gradation ATB mixture, GSOG, was designed. Its design method was proposed based on the volume design method and performance tests. Firstly, several gradations were designed preliminarily in which middle particle sizes of coarse aggregates were partially or completely gapped according to the gradation specification. Secondly, their voids in coarse aggregates (VCA) were determined through dry rod compaction test on coarse aggregates, and then their theoretical voids were calculated. Gradations whose theoretical voids met the requirements were selected to fabricate specimens with Superpave Gyratory Compactor, and their voids were determined using vacuum sealing method and submerged weight in water method. Finally, gradations whose voids meet requirements were selected to fabricate different types of specimens for various performance tests, and the optimal gradation can be selected comprehensively considering their performances, especially focusing on their crack resistance. According to this gradation design method, the gradation of GSOG-25 was designed, and its performances, including high-temperature stability, water stability, fatigue, and antireflection crack resistance, were measured and compared to ordinary ATB-25. The results demonstrate that the performance of GSOG-25 is much better than that of ordinary ATB-25, especially in anticracking capacity.